2020
DOI: 10.1186/s12917-020-02496-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an in-house indirect enzyme-linked immunosorbent assay of feline panleukopenia VP2 subunit antigen in comparison to hemagglutination inhibition assay to monitor tiger antibody levels by Bayesian approach

Abstract: Background: Feline panleukopenia virus (FPV) is an etiologic pathogen of feline panleukopenia that infects all members of Felidae including tigers (Panthera tigris). Vaccinations against FPV among wild felid species have long been practiced in zoos worldwide. However, few studies have assessed the tiger immune response post-vaccination due to the absence of a serological diagnostic tool. To address these limitations, this study aimed to develop an in-house indirect enzyme-linked immunosorbent assay (ELISA) for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…The optimization of an in-house ELISA was modified from a previously described method [ 12 ]. A total of 50 sera samples were derived from infected cattle exhibiting classical cinical signs of LSDV infection and confirmed with the VN assay.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The optimization of an in-house ELISA was modified from a previously described method [ 12 ]. A total of 50 sera samples were derived from infected cattle exhibiting classical cinical signs of LSDV infection and confirmed with the VN assay.…”
Section: Methodsmentioning
confidence: 99%
“…It has a cheaper cost than the VN assay and can be administered more efficiently to a large number of samples on 96 well-plates [ 8 ]. This method has been successfully applied and performed in the detection of certain antibodies to animal diseases [ [9] , [10] , [11] , [12] , [13] ] but would require the use of a standard coated antigen in the microtiter plates [ 8 ]. Previous investigations have demonstrated that ELISA can serve as an efficient diagnostic tool for antibody detection of LSD in animals [ 6 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sera were obtained from the Sample Bank of the Veterinary Diagnostic Laboratory, Faculty of Veterinary Medicine, Chiang Mai University, Thailand. The percentage of binding (% binding) for the sera-to-antigen ratio was compared to that of the elephant at 100% of the 15 µg/mL antigen concentration, as has been previously described [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, a Bayesian latent class analysis was performed to address these problems because this method has inferred posterior estimates from a combination of prior information and observed data to solve the uncertainty of unknown parameters such as test performance or disease prevalence [ 9 ]. This analysis has become increasingly used in veterinary epidemiology to evaluate the accuracy of a diagnostic test or the true disease prevalence when a gold standard may be impossible to obtain [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%